(untitled) (Medico Legal Update, 2020)
Background- Balance disorder is a common problem in post-TBI patients. In many research’s done before treatment is given mainly on motor component to improve balance in TBI patients. In this study we are going to give multidimensional protocol - sensory stimulations along with motor components. Balance is a main component of a patient for his mobility, many therapist concentrate on balance in chronic stage of TBI patients, in this study we are going to give treatment in acute stage of TBI patients which will help them to recover fast. There is lack of research’s done on acute post TBI patients with multidimensional exercise program for balance disorder. Indeed this made us to study the effect of multidimensional exercise program on balance disorder in TBI patients. Objectives- To find out the effectiveness of multidimensional exercise program for improving balance control in mild TBI patients. To find out the effectiveness of multidimensional exercise program for improving balance control in moderate TBI patients. To find out the effectiveness of multidimensional exercise program for improving balance control in severe TBI patient. METHOD- In this study total 20 candidates were taken having impaired balance secondary to TBI from hospitals in karad. Their balance were assessed by berg balance scale and community balance and mobility scale. They were divided into mild, moderate and severe TBI. A multidimensional exercise protocol of 6 week was given for improving balance and their balance was checked at 2nd, 4th, and 6th week by same BBS and CBMS score. Later evaluation and interpretation of data was done. Result- The 20.8% improvement is seen in pre and post treatment BBS score and 8.82% improvement is seen in pre and post treatment CBMS score in post TBI patients with balance impairment. Conclusion- On the basis of result it can be concluded that multidimensional exercise program is effective for improving balance in TBI patients.